Inforg: A Boundary Between Nature and Technology? - Giorgio, Giovanni (Concilium, 2021)
Going beyond the debate raised by the cyborg theme, the author examines the philosophical position of Luciano Floridi, who believes that ICT (Information and Communication Technologies) does not consist merely in applications which improve. Rather, the current computational ubiquity is generating a new environment, the "infosphere", which entails a new ontology and a new macroethics. The first is based on the concept of "informational object", and the second on an ontocentric vision that includes every entity, natural or artificial. The outcome is a "holistic environmentalism" that promises a fruitful and symbiotic relationship between technique and nature.